Biocontrol potential and action mechanism of Bacillus amyloliquefaciens DB2 on Bipolaris sorokiniana - Luan, Pengyu; Yi, Yanjie; Huang, Yifan; Cui, Liuqing; Hou, Zhipeng; Zhu, Lijuan; Ren, Xiujuan; Jia, Shao; Liu, Yang (Frontiers in Microbiology, 2023)
Introduction Bipolaris sorokiniana is the popular pathogenic fungi fungus which lead to common root rot and leaf spot on wheat. Generally, chemical fungicides are used to control diseases. However, the environmental pollution resulting from fungicides should not be ignored. It is important to study the mode of antagonistic action between biocontrol microbes and plant pathogens to design efficient biocontrol strategies. Results An antagonistic bacterium DB2 was isolated and identified as Bacillus amyloliquefaciens. The inhibition rate of cell-free culture filtrate (CF, 20%, v/v) of DB2 against B. sorokiniana reached 92.67%. Light microscopy and scanning electron microscopy (SEM) showed that the CF significantly altered the mycelial morphology of B. sorokiniana and disrupted cellular integrity. Fluorescence microscopy showed that culture filtrate destroyed mycelial cell membrane integrity, decreased the mitochondrial transmembrane potential, induced reactive oxygen species (ROS) accumulation, and nuclear damage which caused cell death in B. sorokiniana. Moreover, the strain exhibited considerable production of protease and amylase, and showed a significant siderophore and indole-3-acetic acid (IAA) production. In the detached leaves and potted plants control assay, B. amyloliquefacien DB2 had remarkable inhibition activity against B. sorokiniana and the pot control efficacy was 75.22%. Furthermore, DB2 suspension had a significant promotion for wheat seedlings growth. Conclusion B. amyloliquefaciens DB2 can be taken as a potential biocontrol agent to inhibit B. sorokiniana on wheat and promote wheat growth.